Crystalline segments in a photo-detachable adhesive. (5th June 2021) - Liu, Ziyu; Wang, Ganyu; Cheng, Jue; Zhang, Junying
Graphical abstract: Highlights: Crystalline segments can improve the bonding strength of light-induced detachable adhesive. Amorphous chain segments still have flexibility to ensure reversible cycloaddition reaction. Linear polyurethane melt has sufficient machinability, this is due to the fast reaction rate of photo-induced reaction. Abstract: Photo-induced detachable adhesive at room temperature is expected in biomedical and expensive precision instruments. However, its concomitant weak bonding strength has been the bottleneck restricting its wide application due to its lower glass transition temperature ( T g ). Herein, a semi-crystalline polyurethane (PU) adhesive was prepared by the reaction of polycaprolactone diol (PCL-diol), 4, 4′-methylenebis (cyclohexyl isocyanate) (HMDI) and chain extender mixture of 1, 4-butanediol (BD) and a diol containing anthracene side chain (AERMT). The anthracene side group was used as the UV light-responsive reversible crosslinking site. The crystalline segments dominated by PCL-diol further enhanced the bonding strength, especially in photo-induced curing adhesive with T g much lower than room temperature. The synthetizing and curing behavior of the adhesive was investigated by FTIR, NMR and UV–vis absorption spectroscopy. DSC, XRD and polarizing microscope were used to confirm the crystallization behavior of the adhesive before and after curing. The bonding strength was tested by using quartz glass sheet as the bonding substrate. The maximum strength was found to reach as high as 7.5 MPa. Then, under the irradiation of 254 nm UV light, the shear strength decreased significantly to achieve the purpose of disassembly process. This study can provide some guidance for photo-induced high strength detachable adhesives at room or moderate temperatures.